Ocenjevanje prostorske zgradbe jelovo-bukovih sestojev - Hladnik, David (Zbornik gozdarstva in lesarstva, 2004)
Stand structures and spatial patterns were studied in three plots in the beechand silver fir forest on the Karst Plateau in Slovenia. We mapped all stems >10 cm in diameter at breast height (dbh) on 2 ha plots. The structure of the forest stands on three research plots varied in stand density and in the spatial distribution of stems, analysed using different methods for the characterisation of spatial distribution of trees. The mean relative differences for measuring tree density were substantially greater for trees 50 cm dbh class were less than 30 %. Based on theoretical models of spatial distribution, a tendency of clustering or clumping of trees was evident in the stand dominated by silver fir. In two beech and silver fir stands, stems were aggregated in large patches of up to 0.5 ha in size. The spatial distribution of silver fir, spruce and beech varied significantly (P<0,01) from a random distribution. Stems of these species aggregated in small and medium patches up to 0.25 ha. Dominant trees were regularly and randomly distributed in the three stands, indicating that after the period of silver fir decline the structure of stands did not deteriorate.
Keywords: jelovo-bukovi gozdovi; porazdelitev; sestoji